MULTICULTURAL EDUCATION; A PLURALISTIC APPROACH IN PREVENTING PRIMORDIALISM IN MADRASAH - Mas'udi, Ahmad Thoyib (EDURELIGIA: Jurnal Pendidikan Agama Islam, 2022)
The purpose of this research is to find out the process of multicultural education that occurs at MA Ihyaul Ulum Dukun Gresik as a pluralistic form of preventing primordialism from entering the world of education. This study used a qualitative approach with a case study type at MA Ihyaul Ulum Dukun Gresik Regency. The data collection technique was through observation, in-depth interviews with 4 informants, namely the head of the madrasah, homeroom teacher for class IX, teacher of aqidah akhlaq subjects, and teacher of Civics. as well as documentation. The data analysis technique uses the Miles and Huberman Interactive Model with data reduction, data display, and conclusion drawing/verification activities. Data validity with source and technique triangulation process. The results of this study indicate the concept of multicultural education carried out by MA Ihyaul Ulum Dukun Gresik as a form of plurality in preventing primordialism in the madrasah environment, namely with the concept of heterogeneous classes, class principles designed "everyone has rights" and establishing ukhuwah interactions. This research will certainly have implications for the development of multicultural educational actions for adolescent students who tend to be sensitive to their thoughts and feelings in the various stimuli presented by the teacher. This research will also open up the potential of multicultural students by upholding high values of moderation and plurality.